CLINICAL PICTURES OF COGNITIVE DYSFUNCTIONS OBSERVED IN ALCOHOLISM - Bobir Temirpulotovich, Turayev (PT. Antis International Publisher, 2025)
Objective: To explore the complications of the nervous system associated with alcoholism and address the gaps in understanding the pathogenesis and effects of ethanol on neural and muscular systems. Methods: A comprehensive review of historical and recent studies on alcoholic lesions of the nervous system was conducted. This involved examining the extent of damage caused by ethanol exposure across various nervous system components and muscles, as well as analyzing the diverse pathogenetic mechanisms underlying these toxic effects. Results: Findings indicate that ethanol exposure results in widespread damage to nearly all parts of the nervous system and muscular structures. The toxic effects are attributed to a variety of pathogenetic mechanisms, which collectively contribute to the complex clinical manifestations of alcohol-induced neurological disorders. Novelty: This study underscores the multifaceted impact of ethanol toxicity, emphasizing the need for a deeper understanding of its pathogenetic mechanisms. It highlights areas where current knowledge is insufficient, paving the way for future research to better address and manage alcohol-related neurological complications.